Legal Position of Political Corruption as Part of Reflection on Money Politics Practices (Law Research Review Quarterly, 2018)
The General Election which was carried out directly was a concrete manifestation of the implementation of democracy in Indonesia. The jargon "of the people by the people and for the people" must be paid at a relatively expensive cost for a clean and correct political contestation to produce the expected leaders. The amount of costs from the implementation side was also followed by the high costs incurred by the candidates for the people's representatives as contestants. Starting from the nomination process through the political vehicle of the bearer to the attempt to seize the prospective voters through various persuasive approaches makes a great potential for the practice of money politics. The causality cycle will have a great opportunity to be reflected in the crime of political corruption. The crime of political corruption is actually not specifically regulated in the legislation but is now becoming familiar. This kind of phenomenon makes the position of criminal act of political corruption worthy of being made a separate offense in a material criminal law regulation. This article is prepared using normative juridical research methods through a statute approach, comparative approach and conceptual approach, which aims to critically examine the legal position of political corruption as part of a reflection of the practice of money politics.